ANALISIS PENGARUH STRATEGIS, OPERASIONAL, DAN ANALITIS CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN DI SUPERMARKET BRAVO JOMBANG - Lailatus Sa’adah (MARGIN ECO, 2018)
This research is aims to know the influence of customer relationship management (CRM) consisting of strategic, operational, and analytical on customer loyalty. The population of this research was the customers of Bravo Jombang Market. The sample of the research was collected by using a sampling purposive method with 100 respodents. The results of this research got regression equation Y = -30,400 + 0,232 X1 + 0,576 X2 + 0,491 X3, so it can be explained that : (1) Strategic has a positive influence but not significance on customer loyalty in Bravo Jombang Market, with 0,232 regression value and 0,473 t arithmetic value with 0,637 significance value; (2) Operational has a positive influence on customer loyalty in the Bravo Jombang Market, with 0,576 regression value and 4,436 t arithmetic value with 0,000 significance value; (3) Analytical has a positive influence on customer loyalty in Bravo Jombang Market, with 0,491 regression value and 5,588 t arithmetic value with 0,000 significance value; (4) Strategic, operational, and analytical simultaneously significant influence on customer loyalty, with 19,016 F arithmetic value and 0,000 significance level, where the significance level is less than 0,05. The results R2 obtain value equal to 0,373, so it can be said that the big influence of strategic, operational, and analytical show that the variable of customer loyalty is 37,3%, and the rest 62,7% from other variables which not having examined in this research. Keywords : Strategic, Operational, Analytical, Customer Loyalty.